The Role of Digital Marketing in Increasing Sales among Halal Micro, Small, and Medium Enterprises (MSMEs) - Dewa Teguh Saputra; Zainal Fattah (EL-IQTISHAD: Journal of Economics, Business and Sharia Studies, 2026)
The rapid development of digital technology has transformed business practices, including those of Micro, Small, and Medium Enterprises (MSMEs). Digital marketing has emerged as an important strategy for improving competitiveness and supporting sales growth, particularly among halal MSMEs. However, studies examining digital marketing in the context of halal MSMEs and Islamic business values remain relatively limited. This study aims to analyze the role of digital marketing in increasing sales among halal MSMEs in Indonesia and to identify the benefits and challenges associated with its implementation. This study employed a descriptive qualitative method with a library research approach. Data were collected from scientific journals, books, and other relevant publications. The findings indicate that digital marketing contributes to sales growth by expanding market reach, enhancing brand awareness, strengthening consumer trust, improving customer engagement, and increasing customer loyalty. In addition, digital marketing provides several benefits, including cost efficiency, broader market accessibility, and improved product visibility. Nevertheless, the implementation of digital marketing still faces challenges such as low digital literacy, limited human resources, financial constraints, and intense market competition. This study contributes to the literature by synthesizing previous findings on digital marketing and highlighting their implications for halal MSMEs within the framework of Islamic business values. Therefore, strengthening digital capabilities and institutional support is essential to optimize sustainable digital transformation among halal MSMEs in Indonesia.